Peak flow assessment of El-Ham wadi in Hodna basin case study - Belazreg, Nour El Houda; Hasbaia, Mahmoud; Şen, Zekai; Ferhati, Ahmed (Springer Heidelberg, 2022)
Wadis of Algeria are subjected to a very irregular hydrological regime. The present study attempts to assess the peak flows in El-Ham wadi study area in the Hodna basin of Algeria by applying empirical (Giandotti, Possenti, Turazza, and Temez) and statistical techniques (Gradex). These methods are the most suitable for El-Ham valley due to the availability and accessibility of precipitation data. The annual maximum daily precipitation (Pmax,d) records are chosen for the applications. This leads, firstly, the estimation of the concentration time T-c using ANRH-Sogreah, Basso, and Giandotti formulas. The results can provide us with many insights. One can easily observe the rise in flood discharges over the different chosen return periods (10-year, 20-year, 50-year, 100-year, and 1000-year). The estimated concentration period equals to 21.5 h. The short-term precipitations at stations 050101, 050301, and 050703 are 91.2 mm, 121.7 mm, and 51.2 mm, respectively, for a 100-year return period. Centennial return period density shows high values at stations 050301 (5.67 mm/h), 2.43 mm/h at station 050703, and 4.25 mm/h at station F050101. Empirical analysis of flood discharges still repeats the same observations regarding flows with return periods with different flow rates (5581.86 m(3)/s for a 100-year, also shown at Ain El Hadjel station). One should point out that these outcomes enhance the future research in the Hodna study area, particularly in study of flash floods which implies the knowledge of peak flow of several return periods.
Keywords: Peak Fow; Hodna; El-Ham Wadi; Empirical Formulas; Gradex; Precipitation